The efficacy of topical agents used in wounds for managing chronic biofilm infections: A systematic review. Issue 3 (March 2020) - Schwarzer, S.; James, G.A.; Goeres, D.; Bjarnsholt, T.; Vickery, K.; Percival, S.L.; Stoodley, P.; Schultz, G.; Jensen, S.O.; Malone, M.
Highlights: In vitro testing accounts for 90% of chronic wound biofilm evidence. In vitro demonstrates iodine as the highest mean log10 reduction (4.81, ±3.14). Heterogeneity between study designs limits the generalisability of results. Lack of in vivo wound biofilm research limits the ability to make recommendations. Abstract: Objectives: Clinicians have increasingly adopted the widespread use of topical agents to manage chronic wound infections, despite limited data on their effectiveness in vivo . This study sought to evaluate the evidence for commonly employed topical agents used in wounds for the purpose of treating chronic infections caused by biofilm. Method: We included in vitro, animal and human in vivo studies where topical agents were tested for their efficacy against biofilms, for use in wound care. For human studies, we only included those which utilised appropriate identification techniques for visualising and confirming the presence of biofilms. Result: A total of 640 articles were identified, with 43 included after meeting eligibility. In vitro testing accounted for 90% ( n  = 39) of all included studies, five studies using animal models and three human in vivo studies. Sixteen different laboratory models were utilised, with the most frequent being the minimum biofilm eradication concentration (MBEC™) / well plate assay (38%, n  = 15 of 39). A total of 44 commercially available topical agents were grouped into twelve categories with the most commonly tested agents being silver, iodine and polyhexamethylene biguanide (PHMB). In vitro results on efficacy demonstrated iodine as having the highest mean log10 reductions of all agents (4.81, ±3.14). Conclusion: There is large disparity in the translation of laboratory studies to researchers undertaking human trials relating to the effectiveness of commercially available topical agents. There is insufficient human in vivo evidence to definitively recommend any commercially available topical agent over another for the treatment of chronic wound biofilms. The heterogeneity identified between study designs ( in vitro to in vivo ) further limits the generalisability of results.